2015
DOI: 10.1016/j.neuroscience.2015.06.055
|View full text |Cite
|
Sign up to set email alerts
|

Neural evidence that suspense narrows attentional focus

Abstract: The scope of visual attention changes dynamically over time. Although previous research has reported conditions that suppress peripheral visual processing, no prior work has investigated how attention changes in response to the variable emotional content of audiovisual narratives. We used fMRI to test for the suppression of spatially peripheral stimuli and enhancement of narrative-relevant central stimuli at moments when suspense increased in narrative film excerpts. Participants viewed films presented at fixa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 39 publications
11
42
0
Order By: Relevance
“…Artistically motivated violations are taken seriously, but dealt with as atypical for the canonical set-up. 34 Bezdek et al (2015) report a study in which participants were shown a film scene at the centre of fixation while checkerboard patterns were flashed in the periphery of vision. The results of fMRI analyses showed that activity of peripheral visual processing areas in the brain was diminished with increasing narrative suspense of the scenes, whereas activity in areas associated with central vision, attention and dynamic visual processing increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Artistically motivated violations are taken seriously, but dealt with as atypical for the canonical set-up. 34 Bezdek et al (2015) report a study in which participants were shown a film scene at the centre of fixation while checkerboard patterns were flashed in the periphery of vision. The results of fMRI analyses showed that activity of peripheral visual processing areas in the brain was diminished with increasing narrative suspense of the scenes, whereas activity in areas associated with central vision, attention and dynamic visual processing increased.…”
Section: Discussionmentioning
confidence: 99%
“…The expectations or questions that guide the gaze may be minimally articulated, e.g., 'what or whom are these characters looking at' as in gaze following, but the operation of higher level cognitive schemas are not excluded. The best demonstration to date of the control of focus of attention by the narrative is given in research on suspense and its effects on film viewer gazes by Bezdek et al (2015) and Bezdek and Gerrig (2017). 34 Their results can be taken to imply that suspense, a state of high absorption, is associated with focal attention to story-world details supervised by expectations created by the narrative (see also Doicaru, 2016).…”
Section: Continuity Of Events and Viewer Attention Hochberg's Questionmentioning
confidence: 99%
“…That is, it may be that suspense heightens the importance of a perceived goal. Indeed, Bezdek and colleagues [ 17 ] tested the hypothesis that, in moments when suspense increases, narrative transportation will produce a changing pattern of activity in brain regions involved in early visual processing. They used fMRI to show that spatially peripheral stimuli received suppressed early visual processing when suspense increased in narrative film scenes.…”
Section: Introductionmentioning
confidence: 99%
“…The implications of these stylistic conventions are twofold: they promote narrative transportation and they elicit overall positive affect in the viewer. In support of the former point, Bezdek et al (2015) demonstrated that an increase in narrative suspense results in reduced activity in brain regions involved in peripheral visual processing, while brain activity associated with central visual processing and attention increases. In other words, the suspense experienced while viewing an action film, as driven by intensified continuity on the filmmaker's part, results in greater visual and cognitive processing of the fiction presented on screen, while reality beyond the screen goes unnoticed by viewers.…”
Section: Open Peer Commentarymentioning
confidence: 69%